2019
DOI: 10.18786/2072-0505-2019-47-073
|View full text |Cite
|
Sign up to set email alerts
|

Is the microvasculature tone increasing with arterial hypertension?

Abstract: Актуальность. Увеличение тонуса сосудов считается одним из важных факторов, приводящих к артериальной гипертонии (АГ). В клинической практике нет методов прямого измерения тонуса сосудов. Косвенно оценить тонус сосудов системы микроциркуляции можно при помощи исследования перфузии методом лазерной доплеровской флоуметрии (ЛДФ). Перфузия характеризует изменение потока крови в единицу времени в анализируемом участке, следовательно, этот параметр должен быть обратно пропорционален тонусу сосудов. Цель -сравнить п… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…It is explained by a decrease in peripheral vascular tone, which is presumably a compensatory reaction of the body in response to increased blood pressure. 4 It was also found that patients with arterial hypertension are characterized by a decrease in vasomotor activity of microvessels with an increase in the tone of the resistive link of the microcirculatory bed against the background of activation of passive mechanisms of blood flow modulation. 5 Many scientists are interested in changing the parameters of LDF in MAH.…”
Section: Introductionmentioning
confidence: 99%
“…It is explained by a decrease in peripheral vascular tone, which is presumably a compensatory reaction of the body in response to increased blood pressure. 4 It was also found that patients with arterial hypertension are characterized by a decrease in vasomotor activity of microvessels with an increase in the tone of the resistive link of the microcirculatory bed against the background of activation of passive mechanisms of blood flow modulation. 5 Many scientists are interested in changing the parameters of LDF in MAH.…”
Section: Introductionmentioning
confidence: 99%